The Effect of Long fermentation of Salak Leaves Using Aspergillus Niger on Physical Quality, pH and Dry Material (BK) as Sheep Feed - Hamdani Azizi, Wisnu; Dian Wulansari, Putri; Ardigurnita, Firgian (Bulletin of Applied Animal Research, 2023)
The problem of adequacy of sheep feed often occurs in developing countries, especially Indonesia. For local sheep farmers who still rely heavily on local feed ingredients, it is often difficult to maintain the availability of forage feed, so farmers need knowledge about the potential of plant waste to be fermented. Fresh salak leaves contain 9.91% crude protein, 2.23% crude fat and 22.9% crude fiber. Fermentation serves as a treatment to preserve ingredients and a way to reduce toxic substances contained in feed ingredients, fermentation can also produce a more favorable aroma than unfermented materials. This study aims to determine the effect of long fermentation of salak leaves using Aspergillus niger on color, aroma, texture, pH, dry matter (BK). The treatment in this study was the addition of Aspergillus niger at levels of 2%, 2%, 2% and 2, 4, 6, 8 days. The results of this study indicate that fermentation of salak leaves using Aspergillus niger 2% with a fermentation time of 2, 4, 6 and 8 days can change the physical characteristics of salak leaves in terms of color, aroma, and texture. Fermentation of salak leaves using Aspergillus niger 2% with fermentation time of 2, 4, 6 and 8 days resulted in the best pH value of 5.38, BK 58.50%. Key words : Aspergillus niger, Fermentation, Salak leaves